Design of Coconut Paring Machine - Karnova Yanel (LP2M - Institut Teknologi Padang, 2018)
Coconut plant is a very useful natural resource for human life. One of the benefits of coconut plant is coconut is a raw material that can be processed fresh drinks. In general, the process of peeling coconut still using the manual process so it takes a lot of energy, a long time, and a sharp tool to peel the coconut, to overcome this need a design of a more efficient young coconut peeler, this machine is designed using cheaper materials so that can be reached by all people especially who have business of coconut sales. Coconut peeler is a working principle of rotary system, the coconut to be peeled is placed on top made specifically for the coconut holder and to ensure the coconut does not fall during peeling process, the coconut is retained using a lever that serves as a lock. The driving force used is the electric motor, power on the electric motor will be forwarded from the pully motor rotation through v-belt to the pulley driven. From this research has been obtained model of machine design to peel coconut coir, coconut coir peel machine which is designed can peel coconut husk within 2 minutes for 1 coconut, with the highest efficiency value which is worth 93.5%